The Performing Arts, the pandemic context, chaos, heterotopias and other knowledge (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article reflects on the experience of a research project that worked with the investigation and experiments of remote practices, from the perspective of acting and theatrical direction at UFSM, and which aimed to reduce damage resulting from the suspension of face-to-face activities in combating the pandemic. Covid-19. In order to think about and problematize this sui generis time and space and the results achieved, this article is based on the Foucauldian and Dubattian perspectives and also discusses epistemological issues.
Keywords: theatrical direction; theater - production and direction; acting; COVID-19 Pandemic, 2020-